2004
DOI: 10.2135/cropsci2004.1315
|View full text |Cite
|
Sign up to set email alerts
|

Differential Sowing Time of Turfgrass Species Affects the Establishment of Mixtures

Abstract: Kentucky bluegrass (Poa pratensis L.) is often poorly established when sown in turfgrass seed mixtures with slender creeping red fescue (Festuca rubra L. ssp. litoralis Vasey) and perennial ryegrass (Lolium perenne L.), possibly because of its slow emergence and slow seedling growth. This study investigated the effect of sowing Kentucky bluegrass earlier than red fescue and perennial ryegrass on the botanical composition of the established turfgrass. In field experiments established during 2 yr, red fescue and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
17
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 17 publications
0
17
0
Order By: Relevance
“…Most KBG and PRG seed mixture ratios are recommended to achieve a 50:50 stand of KBG:PRG because this is simplistically proposed to be an ideal ratio for a mature turfgrass stand (Gibeault et al, 1980). Furthermore, the turf stand ratio of 50:50 KBG: PRG has been frequently targeted in research studies Duich, 1984a, 1984b;Larsen et al, 2004;Larsen and Bibby, 2005;Stier et al, 2005). Similar to our study, Brede (1982) reported a stand initially dominated by PRG eventually shifted to a predominantly KBG stand.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most KBG and PRG seed mixture ratios are recommended to achieve a 50:50 stand of KBG:PRG because this is simplistically proposed to be an ideal ratio for a mature turfgrass stand (Gibeault et al, 1980). Furthermore, the turf stand ratio of 50:50 KBG: PRG has been frequently targeted in research studies Duich, 1984a, 1984b;Larsen et al, 2004;Larsen and Bibby, 2005;Stier et al, 2005). Similar to our study, Brede (1982) reported a stand initially dominated by PRG eventually shifted to a predominantly KBG stand.…”
Section: Resultsmentioning
confidence: 99%
“…Brede (1982) also suggests the presence of PRG may further reduce KBG seedling survival as a result of allelopathic effects. To compensate for PRG's competitive advantage during germination, suggested seed mixtures comprise between 50% and 95% KBG by weight (Brede and Duich, 1984a;Gibeault et al, 1980;Larsen et al, 2004;Larsen and Bibby, 2005), which is between 80% and 98% KBG by seed number. In addition to the seeding ratio of PGR and KBG, several other factors may affect shortterm composition of the turf stand.…”
mentioning
confidence: 99%
“…An equivalent amount of KBG and PRG is often desired in a sward with the intent to prevent significant damage whenever one species is susceptible to a particular biotic or abiotic stress. Previous research has indicated that anywhere from 50% to 95% KBG seed by weight was needed to obtain a 50:50 sward mixture with PRG as a result of slow germination of KBG Duich, 1984a, 1984b;Larsen et al, 2004;Larsen and Bibby, 2005;Stier et al, 2005). In some cases, a 100% PRG seed mix may be necessary and practical depending on the time of year sown.…”
mentioning
confidence: 99%
“…Fairways in the Nordic countries are usually established using a seed mixture of Festuca rubra L., Lolium perenne L., and Poa pratensis L. Poa pratensis is wanted on fairways due to its high recuperative capacity, but overseeding is questionable because it germinates slowly and does not establish easily in competition with other grasses (Larsen et al, 2004; Larsen and Bibby, 2005; Aamlid et al, 2012). Lolium perenne germinates fast, and F. rubra is a reasonable choice for overseeding if a course wants to reduce the inputs of water and fertilizers (Kvalbein et al, 2016).…”
mentioning
confidence: 99%
“…with other grasses (Larsen et al, 2004;Larsen and Bibby, 2005;Aamlid et al, 2012). Lolium perenne germinates fast, and F. rubra is a reasonable choice for overseeding if a course wants to reduce the inputs of water and fertilizers (Kvalbein et al, 2016).…”
mentioning
confidence: 99%